(untitled) (Jurnal Ilmu Komunikasi, 2024)
This research was conducted with the aim of knowing the interpersonal communication of used clothing traders at Senen Market Block 3 in buying and selling activities, negotiations in used clothing buying and selling transactions and the media used by used clothing traders at Senen Market Block 3 in buying and selling activities. This research uses a qualitative descriptive method and the data collection methods used are observation, documentation and interviews with informants in the research. The theory used in this research is the theory of symbolic interaction and media richness. The paradigm used in this research is the constructivist paradigm. The results of this research state that interpersonal communication in buying and selling used clothes at Pasar Senen Block 3 is two-way, which is usually started by the trader by greeting the customer and in serving the customer during the sale, the trader explains the used clothing product he wants to purchase. by customers to provide information related to products and also attract interest and good relations with customers. Negotiations in buying and selling used clothing are a common thing that is carried out with a WIN-WIN strategy to reach a mutually beneficial price agreement. Pasar Senen Blok 3 used clothing traders also sell using media which can make it easier for traders to make sales and can reach customers widely.